CONTROVERSY OVER MANGASE UDAN RITUAL AT SIANJUR MULAMULA DISTRICT, SAMOSIR REGENCY, NORTH SUMATRA - Siregar, Mangihut; Kumbara, A.A. Ngurah Anom; Wirawan, A.A. Bagus (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2018)
The mangase udan ritual is a Batak tradition when they still embrace the Parbaringin school. This ritual is done when they face a prolonged dry season. The entry of the Dutch colonial to the Tapanuli region, as well as the broadcast of religion make this ritual becomes a forbidden tradition. On October 10, 2016, the mangase udan ritual was performed again at Dolok Simanggurguri, Sianjur District, Mulamula District, Samosir Regency, North Sumatera. The implementation of the ritual mangase udan experience pros and cons in society. To explore this pro and contra attitude, it is necessary to conduct research which is aimed to know how the implementation of mangase udan ritual does; why there is controversy about the ritual; and what are the implications of the mangase udan ritual controversy. The method used in this research is qualitative method. Theories used to analyze the problems are power/knowledge (discourse) theory, postcolonial theory, and social practice theory. The results showed that the mangase udan ritual was carried out in Sianjur Mulamula District due to a prolonged drought. Through the implementation of the mangase udan ritual, the stoning kings wanted to show their existence. The Catholic Church supports the implementation of the mangase udan ritual in order to broadcast the religion while the Christian church rejects it for the reasons that it is in contrary with Christianity. The implications of the mangase udan ritual controversy are the increasingly high polarization between the Christianity and the Catholicism. There is another implication that is the Catholic religion has good relation with the government and the relationship between Christianity and the government is not good.